Роль держави в розвитку венчурного фінансування в Україні - Хорт, Ю. В.; Хорт, Ю. В.; Hort, Ju. (Одеса : Юрид. л-ра, 2014)
In article the author analyses the modern state of state support of venture capital financing in Ukraine; the role of state in the building of venture capital market in Ukraine.
Хорт Ю. В. Роль держави в розвитку венчурного фінансування в Україні / Ю. В. Хорт // Актуальні проблеми держави і права: зб. наук.пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.]; МОН України, НУ ОЮА. – Одеса: Юрид. л-ра, 2014. – Вип. 71. - С. 50-55.
Keywords: венчурний фонд; венчурний капітал; інновації.; венчурный фонд; венчурный капитал; инновации; venture fund; venture capital; innovations